THE IMPLEMENTATION OF SCORE STRATEGY IN TEACHING READING COMPREHENSION - Alex Sandra (ELP (Journal of English Language Pedagogy), 2021)
The purpose of this study was to determine the extent to which Score Strategy may increase students' reading comprehension and the factors that improved students' reading comprehension at Grade XI of the Office Administration Program of SMK Budi Mulia. This research was classroom action research. The subject of this research was the XI students of the Office Administration Program at SMK Budi Mulia. The instrument of this research was a test, observation, field note, and interview. The research was conducted in two cycles which included plan, action, observe, and reflect. The finding of this research showed that the students reading comprehension at the XI student of SMK Budi Mulia had significant improvement after using the SCORE Strategy. The improvement was influenced by several factors; teaching material, media, classroom activities, classroom management, teacher’s strategy.